Amino Acid Derivatives of Tetrathiafulvalene and Their N–H···O Peptide Bond Dipoles‐Templated Solid State Assemblies. Issue 5 (19th December 2012) - El‐Ghayoury, Abdelkrim; Zorina, Leokadiya; Simonov, Sergey; Sanguinet, Lionel; Batail, Patrick
Abstract: We report on a series of amino acid derivatives of tetrathiafulvalene as well as on the structure‐directing abilities of their peptide residues in the crystalline solid state to stabilize patterns of interactions such as β strands and sheet motifs. Characteristic hydrogen‐bonding motifs are indeed identified within ethylenedithiotetrathiafulvalene (EDT‐TTF) and dimethyltetrathiafulvalene (Me2 ‐TTF) based compounds1 –5 . Esters1 –3 contain hydrogen‐bond acceptors, namely carbonyl groups, as well as one strong (NH) and one weak (C  sp   2 –H) hydrogen‐bond donor. In addition to the hydrogen‐bonded sets of ester derivatives, acids4 and5 present the carboxylic acid moiety, which acts as both a hydrogen‐bond donor and acceptor. EDT‐TTF‐CO‐GlyOH has been previously used to afford a new type of hydrogen‐bonded acid/zwitterion (1:1) hybrid admixture of redox peptidics. Abstract : The synthesis of a new series of amino acid‐appended ethylenedithiotetrathiafulvalene or dimethyltetrathiafulvalene cores reveals three characteristic hydrogen‐bonding types of interactions that effectively direct self‐assembly in the solid state.